Phytochemical notes on cissampelos spp (1995)
Phytochemical and pharmacological aspects of Cissampelos ovalifolia D. C. and C. pareira L. from Guyana, India and several regions of Colombia are discussed. A description of extraction procedures, isolation, purification, chromatographic (CC, TLC) and spectroscopic techniques (IR, H +-NMR, MS) as well as a comparison of the BBI alkaloids present in the material studied,are presented.